The Indigenous-led regional development in Delanggu and Juwiring Districts of Indonesia through the design approach of “Flowering of the Total Person” / Pandu Purwandaru, Toufiq Panji Wisesa and Teddy M. Darajat - Pandu, Purwandaru; Toufiq Panji, Wisesa; Teddy M., Darajat (Universiti Teknologi MARA, Perak, 2018)
Delanggu-Juwiring districts are located in Central Java Province, Indonesia, have a very close relationship with rice farming activities since the beginning of the Javanese kingdom era. This strong association produced 2 characteristics which became the identity of the society in Delanggu and Juwiring: (1) the pattern of traditional rice farming activities, and (2) the local rice variety. Based on the findings from the main author, there were 3 main activities in rice cultivation process in Delanggu and Juwiring: farming, making crafts, and rituals. While from rice variety aspect, Rojolele is a local high quality (both taste of rice and rice straw for craft making material) grown from the geographic characteristic both in Delanggu and Juwiring. After the Green Revolution initiated by the government in 1967, the traditional rice farming pattern gradually transformed into industrial based farming which focusing only on rice production quantity. Despite the success of the program, the society now facing a problem in social, cultural and environmental aspects. To prevent these conditions, as an effort to redevelop the region of Delanggu-Juwiring, a project was held based on the Flowering of the Total Person/人身の花 (read: Jinshin no hana) concept. This way of thinking advocated by Emeritus Professor Kiyoshi Miyazaki of Chiba University and describes a holistic design approach for “designing living” which has a strong emphasis in social and ecological consciousness. Through close cooperation and active participation with village people as the requirement for this concept, the design team was supporting the locals on improving craft design, and formulating a tourism promotional idea. In running this project, the first phase is exploring “being” as an actual existence of “treasures” in local’s area. After the “being” was explored, the next phase is formulating “what should be” design ideas with local community, continued with implementation. This project produced 2 outputs: the development of rice straw crafts based on local needs and a plan of a traditional festival of rice culture activities.